The 4th Philippine graduate tracer study examining higher education as a pathway to employment, citizenship, and life satisfaction from the learner's perspective - Tutor, Melba, V.; Orbeta, Aniceto C. Jr; Miraflor, James Matthew B. (Research paper series, 2021)
This study reports on the 4th Philippine Graduate Tracer Survey results, covering graduates from academic years 2008–2009, 2009–2010, and 2010–2011. The results show that graduates are motivated by earnings and career advancement in their choice of baccalaureate programs, and their choices are concentrated in a few courses. There are also telltale signs of job-education mismatch, with only 49 percent of graduates who took courses requiring a professional license employed in jobs that match their degree. Meanwhile, despite being concerned about their earnings and rating themselves low in financial condition, overall life satisfaction is high among graduates. In relating college experience to postcollege life, this study finds that positive college experience (in its multiple dimensions) is generally associated with better employability, a stronger sense of citizenship, less predisposition to political action, and better life satisfaction. --Back cover.